1983
DOI: 10.1212/wnl.33.4.424
|View full text |Cite
|
Sign up to set email alerts
|

The relation of cembral vasospasrn to the extent and location of subarachnoid blood visualized by CT scan

Abstract: In 41 cases of verified ruptured saccular aneurysm, we prospectively predicted the presence or absence of delayed symptomatic cerebral vasospasm. CT criteria quantifying the extent and location of subarachnoid blood (developed in our previous retrospective study) were used in this prospective series of patients. Twenty-two patients had recognizable subarachnoid clots larger than 3 X 5 mm or layers of blood more than 1 mm thick (measured on reproduced images). In 20 of the 22 patients with severe significant cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(25 citation statements)
references
References 0 publications
3
21
0
1
Order By: Relevance
“…Fisher et al [5]and Fisher [26]stated that blood localized in the subarachnoid space was the most important causative factor in vasospasm. This observation has been confirmed by several authors [6, 7, 8], and results of the current study further support this notion. It was stated that the failure to prevent vasospasm may have been related to the failure of removing subarachnoid clot adequately or promptly.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Fisher et al [5]and Fisher [26]stated that blood localized in the subarachnoid space was the most important causative factor in vasospasm. This observation has been confirmed by several authors [6, 7, 8], and results of the current study further support this notion. It was stated that the failure to prevent vasospasm may have been related to the failure of removing subarachnoid clot adequately or promptly.…”
Section: Discussionsupporting
confidence: 93%
“…Although 40–70% of patients develop arterial narrowing, only 20–30% will manifest neurological deficits [1, 2, 3, 4]. The amount of blood in the basal cisterns detected on the initial computed tomography (CT) scan is highly predictive of the risk of delayed ischemia and infarction [5, 6, 7, 8]. Although the effect of treatment used for the aneurysm on the incidence of cerebral vasospasm and consequent delayed ischemic neurologic deficit is largely unknown, previous reports have suggested that vasospasm might be prevented by clot removal within 48–72 h of SAH [9, 10, 11, 12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, in clinical studies of aSAH, patients with SAH of Fisher Grades 1, 2, and 3 have an escalating degree of disability, but patients with Grade 4 SAH have a disability that falls between that of 2 and 3. 9,11 The modified Fisher scale corrects this problem but was not available for all patients in the study and could not be used. To correct for the lack of linearity, the Fisher score was recoded so that Fisher Grade 4 hemorrhages (diffuse or no subarachnoid blood with cerebral or ventricular blood) were given a value of 3 and Fisher Grade 3 hemorrhages (localized clot and/or vertical layers of blood) a value of 4 The Fisher grade is reported in the original form (Fisher Grade 3 = localized clot and/or vertical layers of blood).…”
Section: Methodsmentioning
confidence: 99%
“…These mechanisms also may be involved in ictal activity, hydrocephalus, and cerebral edema after SAH. The robustness of these molecular events seems to depend on the severity of the hemorrhage and the presence of intraventricular blood (7,28,47,52).…”
mentioning
confidence: 99%